A rare diving beetle from Baltic amber: Hydrotrupes prometheus new species reveals former widespread distribution of the genus (Coleoptera, Dytiscidae). (July 2014) - Gómez, R. Antonio; Damgaard, Anders L.
Abstract : A new species in the extant genus, Hydrotrupes Sharp, H. prometheus n. sp., (Coleoptera, Dytiscidae) is described from Baltic amber (Eocene) based on examination of a single female specimen. This description represents one of a limited number of diving beetle taxa described from fossiliferous amber and is currently the oldest known fossil assigned to Agabinae. Based on this specimen Hydrotrupes is at least 40 million years old. The occurrence of Hydrotrupes during the Eocene suggests that the current disjunct distribution of living Hydrotrupes species occurring in western North America and eastern China is a relict of former widespread distribution in the northern continents. Considering the age of this fossil and its similarity to living members of the genus Hydrotrupes, the conservation of morphology in this lineage of diving beetles is notable. Key morphological characters of the new species are illustrated, and the significance of this discovery for understanding Agabinae evolution and the biogeography of this previously hypothesized trans-Beringian lineage is discussed.